ANALISIS LAPORAN KEUANGAN TERHADAP PENILAIAN KINERJA KEUANGAN PT TRANS MULTI CARGO KOTA BATAM - Bedaru, Adi; Effendi, Syahril (LPPM Universitas Putera Batam, 2023)
This study aims to determine the company's financial performance as assessed by financial ratio analysis at PT. Trans Multi Cargo from 2018 to 2021. The data analysis method used is a quantitative descriptive method using measurements of liquidity ratios, solvency, activity and profitability. based on the results of research on the liquidity ratio in the 2018-2021 period it can be said that it is not good because the company has difficulty paying off current liabilities using current assets owned by the company. Based on solvency in the 2018-2021 period, it is quite good where it has increased every year, this is due to low corporate spending originating from loans. Based on activities in the 2018-2021 period, it is quite good where every year there is an increase in this situation. This situation must be maintained so that the use of company assets is more effective and efficient. Meanwhile, based on profitability in the 2018-2021 period, this shows an increase in profits or profits generated in the company